Phytochemical Analysis and Antioxidant Activity Test of Bayur Medicinal Plants (Pterospermum Javanicum) - Abdul Hapid (Postgraduate, University of Mataram, 2023)
Bayur (Pterospermum javanicum) is a plant species from the Malvaceae family which is a medicinal plant that is often found in Indonesia, especially in the forests of Central Sulawesi. Bayur leaf extract is used as an external medicine, namely to treat back pain, sprains, gout, scabies, cysts, itching, peeling skin and festering wounds. As an internal medicine, namely to treat diarrhea, gastrointestinal disorders, respiratory disorders, lowering high blood pressure, insomnia, blood urine and as a cosmetic. This study aims to screen phytochemicals and analyze the antioxidant activity of bayur medicinal plants. The method used for the phytochemical test is a qualitative method by observing the change in color and shape of the liquid after testing. The DPPH method was used to determine its antioxidant activity. The results showed that bayur leaf extract contained alkaloids, flavonoids, tannins, steroids and terpenoids, while bayur bark positively contained alkaloids, flavonoids, tannins and terpenoids. The results of the antioxidant activity test of bayur leaf and bark extracts using the DPPH method, bayur leaves have an IC50 of 62.438 ppm and bayur bark has an IC50 of 75.878 ppm. The antioxidant activity of bayur leaves and skin is in the strong category Â